Composite of Peptide‐Supramolecular Polymer and Covalent Polymer Comprises a New Multifunctional, Bio‐Inspired Soft Material. Issue 18 (26th July 2019) - Chakraborty, Priyadarshi; Ghosh, Moumita; Schnaider, Lee; Adadi, Nofar; Ji, Wei; Bychenko, Darya; Dvir, Tal; Adler‐Abramovich, Lihi; Gazit, Ehud
Abstract: Peptide‐based supramolecular hydrogels are utilized as functional materials in tissue engineering, axonal regeneration, and controlled drug delivery. The Arg‐Gly‐Asp (RGD) ligand based supramolecular gels have immense potential in this respect, as this tripeptide is known to promote cell adhesion. Although several RGD‐based supramolecular hydrogels have been reported, most of them are devoid of adequate resilience and long‐range stability for in vitro cell culture. In a quest to improve the mechanical properties of these tripeptide‐based gels and their durability in cell culture media, the Fmoc‐RGD hydrogelator is non‐covalently functionalized with a biocompatible and biodegradable polymer, chitosan, resulting in a composite hydrogel with enhanced gelation rate, mechanical properties and cell media durability. Interestingly, both Fmoc‐RGD and Fmoc‐RGD/chitosan composite hydrogels exhibit thixotropic properties. The utilization of the Fmoc‐RGD/chitosan composite hydrogel as a scaffold for 2D and 3D cell cultures is demonstrated. The composite hydrogel is found to have notable antibacterial activity, which stems from the inherent antibacterial properties of chitosan. Furthermore, the composite hydrogels are able to produce ultra‐small, mono‐dispersed, silver nanoparticles (AgNPs) arranged on the fiber axis. Therefore, the authors' approach harnesses the attributes of both the supramolecular‐polymer (Fmoc‐RGD) and the covalent‐polymer (chitosan) component, resulting in a composite hydrogel with excellent potential. Abstract : A composite of minimalistic tripeptide Fmoc‐RGD and chitosan results in a thixotropic and mechanically stable hydrogel, capable of 2D and 3D cell culture. These hydrogels are also antibacterial and can produce ultra‐small silver nanoparticles from diffused solar radiation.